Bentuk Penyajian Tidi Lo Tabongo pada Acara Pagelaran Seni Budaya di Kecamatan Tapa - Mayang, Srisusanti; Djafar, Nurlia; Sitharesmi, Riana Diah; Karlan, Iaode; Pulukadang, Mimy Astuty (Pusat Riset dan Inovasi Nasional, 2026)
Tidi Lo Tabongo is one of the classical dances included among the eight types of Tidi. Tidi Lo Tabongo means a warding-off dance or a dance to be cautious of something; however, it is not ritualistic and is commonly performed at the bridal procession of Gorontalo princesses by men from outside Gorontalo or during guest welcoming events. This study aims to describe the performance form of Tidi Lo Tabongo in the Tapa District of Gorontalo using Janet Adshead’s theory as presented in Riana Diah Sitharesmi’s book and A.A.M. Djelantik’s aesthetics theory. The purpose of the research is to identify and describe the performance form and components of Tidi Lo Tabongo Gorontalo. This study employs a qualitative approach with a descriptive nature as the basis for information processing. Data collection began with initial observations, followed by interviews with informants and direct review of Tidi Lo Tabongo performances. All observation results were recorded and compiled in visual documentation, including images and audiovisual recordings. The analysis shows that Tidi Lo Tabongo is performed by four Gorontalo female dancers wearing traditional Galenggo attire, featuring four main movement variations and eight floor patterns, accompanied by Tidi Lo Tabongo songs and Rebana musical instruments. The dance symbolizes vigilance and strives to create a sense of comfort for visiting guests, representing Gorontalo culture, particularly the personality of Gorontalo women in fostering safety, comfort, and harmony, while remaining free from negative influences.